Plant U-Box40 Mediates Degradation of the Brassinosteroid-Responsive Transcription Factor BZR1 in Arabidopsis Roots. Issue 4 (27th February 2019) - Kim, Eun-Ji; Lee, Se-Hwa; Park, Chan-Ho; Kim, So-Hee; Hsu, Chuan-Chih; Xu, Shouling; Wang, Zhi-Yong; Kim, Seong-Ki; Kim, Tae-Wuk
Abstract : Brassinosteroid signaling tightly controls the degradation of the transcription factor BRASSINAZOLE RESISTANT1 specifically in roots. Abstract: Brassinosteroid (BR) regulates a wide range of physiological responses through the activation of BRASSINAZOLE RESISTANT1 (BZR1), whose activity is tightly controlled by its phosphorylation status and degradation. Although BZR1 appears to be degraded in distinct ways in response to different hormonal or environmental cues, little is known about how BR signaling regulates its degradation. Here we show that the BR-regulated U-box protein PUB40 mediates the proteasomal degradation of BZR1 in a root-specific manner in Arabidopsis ( Arabidopsis thaliana ). BZR1 levels were strongly reduced by plant U-box40 (PUB40) overexpression, whereas the pub39 pub40 pub41 mutant accumulated much more BZR1 than wild type in roots. The bzr1 - 1D gain-of-function mutation reduced the interaction with PUB40, which suppressed PUB40-mediated BZR1 degradation in roots. The cell layer-specific expression of PUB40 in roots helps induce selective BZR1 accumulation in the epidermal layer. Both BR treatment and loss-of-function of PUB40 expanded BZR1 accumulation to most cell layers. In addition, BZR1 accumulation increased the resistance of pub39 pub40 pub41 to low inorganic phosphate availability, as observed in bzr1 - 1D . BRASSINOSTEROID-INSENSITIVE2-induced phosphorylation of PUB40, which mainly occurs in roots, gives rise to BZR1 degradation through enhanced binding of PUB40 to BZR1 and PUB40's stability. Our results suggest a molecular mechanism of root-specific BZR1 degradation regulated by BR signaling.